The deferral of attacks: SP/A theory as a model of terrorist choice when losses are inevitable - Peter J. Phillips; Gabriela Pohl (Open Economics, 2018)
When a terrorist group's aspirations far exceed the outcomes that can be expected to result from any of the available attack methods, an outcome below the terrorist group's aspiration level is inevitable. A primary prediction of SP/A theory when applied to the study of terrorist behaviour is that when losses are inevitable the terrorist group will be risk averse and inclined to defer further action until expected outcomes improve, new attack method innovations are developed or the memory of the event that shaped aspirations has faded sufficiently that the aspiration level can be "reset". This complements existing predictions of loss aversion and risk seeking behaviour over the domain of avoidable losses and provides a starting point for developing explanations for patterns of behaviour that are observed in the terrorism context, including pauses in violence, even during brutality contests, and time-lags between terrorist attacks.
Keywords: 330; SP/A Theory; Terrorist Behaviour; Risk; Uncertainty; Inevitable Losses; Aspiration; Brutality; Violence; Contests; Attacks; Avoidable Losses